Zooplankton species composition and diversity in the seagrass habitat of Lawas, Sarawak, Malaysia - Ismail, Johan; Mustafa Kamal, Abu Hena; Idris, Mohd Hanafi; Amin, S. M. Nurul; Hamli, Hadi; Sien, Leong Sui; Al-Asif, Abdulla; Abualreesh, Muyassar (Pensoft Publishers, 2021)
Seagrass habitats are considered to be some of the most biodiverse ecosystems on the planet and safeguard some ecologically and economically important fauna, amongst which are some globally threatened species, including dugong. Malaysian seagrass ecosystems are not widespread, but their existence supports some significant marine fauna. A rigorous zooplankton study was conducted from May 2016 to February 2017, in the seagrass habitat of Lawas, Sarawak, Malaysia, to examine their temporal composition and diversity, together with their ecological influences. A total of 45 zooplankton species from 13 significant groups were recorded in the seagrass habitat. The population density of zooplankton ranged between 2,482 ind/m³ and 22,670 ind/m³ over three different seasons. A single zooplankton copepod was found to be dominant (47.40%), while bivalves were the second largest (31.8%) group in terms of total abundance. It was also noticed that the average relative abundance (0.62) and important species index (62.08) of copepods were higher than for other groups that exist in the seagrass meadow, whereas copepod Parvocalanus crassirostris showed both the highest average relative abundance (0.41) and the highest important species index (41.15). The diversity (H') and richness index of the intermediate season were found to be highest due to favourable physico-chemical conditions. Within the referred seasonal cluster, the wet and dry seasons were almost similar in terms of species abundance, while the intermediate season was distinct, with high species diversity backed by ANOSIM analysis results. Copepod and bivalves formed one group with a common similarity level of 0.80. The CCA (Canonical Correspondence Analysis) model established that abiotic factors, especially turbidity, NO2, rainfall, dissolved oxygen and pH were significantly correlated with abundance of individual groups of zooplankton. Zooplankton assemblage and abundance in Lawas were found to be very rich in multiple seasons, indicating that the productivity of uninterrupted seagrass habitat might be high and the system rich in biodiversity.